2017
DOI: 10.18203/2394-6040.ijcmph20174259
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study to assess the modifiable risk factors and morbidity profile of elderly people in a village in tribal part of Maharashtra

Abstract: Background: Geriatrics population is an important part of the total community and comprises of about 7-8% of the whole population of one community. Since the expectation of life is also increasing steadily and quality of life being emphasized more & more in our country, the senior citizen group is getting importance day by day. The present study was carried to find the various social, economical and medical aspects related to geriatrics population in rural area. Methods: The community based cross sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…their inability to work. 17,18 The inability status of elderly to work is a physiological phenomenon, but the consequences may lead to a state of financial dependency. Also, lack of individual income as reported by males (8%) and females (20%) could be taken as financial dependency.…”
Section: Discussionmentioning
confidence: 99%
“…their inability to work. 17,18 The inability status of elderly to work is a physiological phenomenon, but the consequences may lead to a state of financial dependency. Also, lack of individual income as reported by males (8%) and females (20%) could be taken as financial dependency.…”
Section: Discussionmentioning
confidence: 99%
“…13 In one of the studies, it was reported that anemia (51%), cataracts (54%), hypertension (26%), arthritis (56%), and chronic bronchitis (6%) were the main illnesses. 14 In another study, it was reported that the most common morbidity among the elderly was pain in the joints and joint stiffness, followed by dental and chewing problems, diminished visual acuity mainly due to cataract and refractive errors, and difficulty in hearing. It was also found that 61% of the people chewed tobacco, 33.3% of males were smokers and 28.7% regularly consumed alcohol.…”
Section: Materials a N D Methodsmentioning
confidence: 99%